2014
DOI: 10.1039/c4fd00041b
|View full text |Cite
|
Sign up to set email alerts
|

Nanodiamond surface redox chemistry: influence of physicochemical properties on catalytic processes

Abstract: Modification of an electrode with an immobilised layer of nanodiamond is found to significantly enhance the recorded currents for reversible oxidation of ferrocene methanol (FcMeOH). Current enhancement is related to nanodiamond diameter, with enhancement increasing in the order 1000 nm < 250 nm < 100 nm < 10 nm < 5 nm. We attribute the current enhancement to two catalytic processes: i) electron transfer between the solution redox species and redox-active groups on the nanodiamond surface; ii) electron transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 26 publications
(52 reference statements)
3
32
0
Order By: Relevance
“…Thus, HMF is partially bonded to the DNP surface. This result agrees well with previous studies, where infrared experiments confirmed the strong electrostatic affinity of the oxidized form of HMF for negatively charged diamond nanoparticles surfaces [17]. The negative charge of commercial DNP powders arises from acid cleaning steps that leave oxygen groups on the surface, particularly carboxyl groups [21][22].…”
Section: Electrochemical Characterization Of Dnps4 Modified Gold Elecsupporting
confidence: 90%
See 3 more Smart Citations
“…Thus, HMF is partially bonded to the DNP surface. This result agrees well with previous studies, where infrared experiments confirmed the strong electrostatic affinity of the oxidized form of HMF for negatively charged diamond nanoparticles surfaces [17]. The negative charge of commercial DNP powders arises from acid cleaning steps that leave oxygen groups on the surface, particularly carboxyl groups [21][22].…”
Section: Electrochemical Characterization Of Dnps4 Modified Gold Elecsupporting
confidence: 90%
“…Depending on the specific synthesis conditions and purification procedures employed in their fabrication, the resulting nanomaterials can present different sizes and physicochemical properties and, therefore, differences in their surface chemistry [14], which clearly affect their subsequent behavior. In particular, previous studies have shown that DNPs diameter has a great influence on their reactivity [17,21]. Thereby, the percentage of the number of atoms on the DNPs surface, the number of functionality groups and the sp 2 /sp 3 carbon ratio are parameters greatly dependent on the size.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Holt and her colleague [60][61][62][63][64][65] made extensive investigation on the electrochemistry of detonation diamond nanoparticles. Differential pulse voltammetry of electrode-immobilised layers of diamond nanoparticles in the absence of solution redox species revealed oxidation and reduction peaks, resulting from direct electron transfer reactions of diamond nanoparticles themselves [60].…”
Section: Detonation Diamond Nanoparticlesmentioning
confidence: 99%